ОРНИТОКОМПЛЕКСЫ РАВНИННЫХ И ГОРНЫХ ЛЕСОВ ЮЖНОГО ВЬЕТНАМА: ВИДОВОЙ СОСТАВ И РАСПРЕДЕЛЕНИЕ ПО ТРОФИЧЕСКИМ ГИЛЬДИЯМ - Трунов, В.Л.; Палько, И.В.; Гоголева, С.С.; Васильева, А.Б.; Чан, Минь Тьен; Калякин, М.В. (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
IN SOUTHERN VIETNAM: SPECIES COMPOSITION AND TROPHIC GUILDS DISTRIBUTIONBird communities were studied during field surveys in five protected forested territories in the south of Vietnam: Yok Don National Park, Dong Nai Biosphere Reserve, Bu Gia Map National Park, Bidoup-Nui Ba National Park and Chu Yang Sin National Park. Lowland communities showed higher species diversity than montane ones. The similarity measure of bird species composition was rather high among three lowland forests and between two montane forests, however, few species were common for both lowland and montane communities. The study of the ecological structure of bird communities was based on trophic guilds composition. Six guilds of forest birds were conventionally defined: insectivore, predatory, frugivore, nectarivore, granivore and omnivore. All guilds were presented in all studied bird communities, but their portion varied between lowland and montane forests. The high similarities of guild proportions between all lowland and both montane forests demonstrated, assumingly, that the found ecological structures are stable for each type of community. Although species composition of trophic guilds varied greatly between lowland and montane communities, the similarity measure was greater among predatory birds and less among “plant-eating” birds (frugivore, nectarivore and granivore guilds combined). Apparently,that reflects greater dependence of “plant-eating” birds upon plant species composition in lowland and montane forests. The complex assessment of bird communities based on species composition and ecological structure can be useful for comparative studies of bird distribution in diverse ecosystems and for temporal monitoring of degrading or restored natural habits.